Geographical analysis of natural resources in Darbandikhan District and investment - Hussein, Hardi Hama Hussain; Amin, Prof.Dr. Hawre Yasin Muhammad Amin Muhammad (Sulaimani Journal for Humanities, 2025)
The district of Darbandikhan is one of the districts of Sulaymaniyah Governorate. The area of the district is 577.8 km2 , constituting 3.48% of the total area of Sulaymaniyah Governorate. The research area focuses on the exploitation of natural resources(soil, wild vegetation, wildlife, and minerals), which will contribute to building a solid infrastructure for both current and future generations. Natural resources are not evenly distributed across the world, the Kurdistan Region, or the study area. This disparity is due to geological formations, rock composition, and geographical locations. Natural resources can be categorized based on their renewability. Some, such as clean energy (widely prioritized in the modern era), are renewable. Others, like mineral minerals, resources, are non-renewable. The quantity and longevity of non-renewable resources depend heavily on extraction methods and utilization rates.
Keywords: Soil; Natural plant; Wild animal; Natural reserve; Minerals resources